2002
DOI: 10.1080/080370502753543954
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Economic Consequences of Cognitive Improvement with Losartan

Abstract: In a clinical trial, treatment of mild-moderate hypertensive patients with losartan (50 mg) increased Mini-Mental State Examination (MMSE) scores by 4 points from baseline over a 26-month period, compared with a 1-point increase in patients treated with hydrochlorothiazide (25 mg). This study explores the potential economic consequences of this improvement in cognitive function in a population of elderly hypertensive patients in Sweden. Resource use and MMSE data for 437 hypertensive, non-demented subjects age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(26 reference statements)
1
1
0
1
Order By: Relevance
“…In human studies, the Losartan Intervention For Endpoint Reduction study (Dahlof et al 2002), the Valsartan Antihypertensive Long-term Use Evaluation study (Julius et al 2004) and the Candesartan in Heart Failure Assessment on Reduction in Mortality and Morbidity study (McMurray et al 1993) reported quality of life (QoL) enhancements following antihypertensive therapy using AIIAs. These were confirmed by further studies, in addition to improved Mini-Mental State Examination (MMSE) scores (Tedesco et al 1999;Jönsson et al 2002;Hanon et al 2008) and improved acquisition and recall (Fogari et al 2003(Fogari et al , 2004(Fogari et al , 2006 in older patients with hypertension. Additionally, Saxby et al (2008) reported that chronic treatment (44 weeks) with candesartan produced protective effects against the deterioration of episodic memory in older patients with hypertension when compared to placebo-treated age-matched patients.…”
Section: Introductionsupporting
confidence: 62%
“…In human studies, the Losartan Intervention For Endpoint Reduction study (Dahlof et al 2002), the Valsartan Antihypertensive Long-term Use Evaluation study (Julius et al 2004) and the Candesartan in Heart Failure Assessment on Reduction in Mortality and Morbidity study (McMurray et al 1993) reported quality of life (QoL) enhancements following antihypertensive therapy using AIIAs. These were confirmed by further studies, in addition to improved Mini-Mental State Examination (MMSE) scores (Tedesco et al 1999;Jönsson et al 2002;Hanon et al 2008) and improved acquisition and recall (Fogari et al 2003(Fogari et al , 2004(Fogari et al , 2006 in older patients with hypertension. Additionally, Saxby et al (2008) reported that chronic treatment (44 weeks) with candesartan produced protective effects against the deterioration of episodic memory in older patients with hypertension when compared to placebo-treated age-matched patients.…”
Section: Introductionsupporting
confidence: 62%
“…In a separate study, Jonsson et al [165] also found that the cognitive improvement associated with losartan treatment of elderly hypertensive patients in Sweden translated into potential economic benefits beyond blood pressure control. Over 26 months, the 4-point improvement in Mini-Mental State Examination scores in losartan-treated patients (compared with a 1-point increase in hydrochlorothiazide-treated patients) was estimated to result in cost savings between SEK24 700 and SEK43 700, a value comparable with the losartan acquisition cost during the treatment period.…”
Section: Cost-effectivenessmentioning
confidence: 95%
“…La possibilità di prevenire efficacemente eventi clinici importanti in soggetti ad alto rischio non è solo un benvenuto progresso clinico, ma ha la potenzialità di incidere sui costi sanitari complessivi delle patologie cardiovascolari. Ciò è stato dimostrato per quanto riguarda il rallentamento della progressione della nefropatia diabetica, in più contesti sanitari, ed è ipotizzabile per altre patologie ad alto impatto economico, il cui rischio viene ridotto da losartan, come gli ictus (LIFE), lo scompenso cardiaco che necessita di ricovero (ELITE, RENAAL), il deterioramento cognitivo [23], l'insorgenza di nuovi casi di diabete.…”
Section: Conclusioniunclassified